2016
DOI: 10.1111/jora.12247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trajectories of Friends' and Parents' School Involvement on Adolescents' Engagement and Achievement

Abstract: In a sample of 527 academically at-risk youth, we investigated trajectories of friends' and parents' school involvement across ages 12–14 and the joint contributions of these trajectories to adolescents' age 15 school engagement and academic achievement. Girls reported higher levels of friends' and parents' school involvement than boys. Both parents' and friends' school involvement declined across ages 12–14. Combined latent growth models and structural equation models showed effects of the trajectories of fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
31
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 76 publications
(76 reference statements)
4
31
0
4
Order By: Relevance
“…Gender effects . The finding that females score higher relative to males on both the general motivation factor and the peer aspirations factor is consistent with prior literature that adolescent females have higher academic self‐efficacy in high school (Caprara et al., ) and report greater peer academic support (Im et al, ; Wang & Eccles, ). The MEA was equally predictive of high school graduation versus dropout status for males and females.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Gender effects . The finding that females score higher relative to males on both the general motivation factor and the peer aspirations factor is consistent with prior literature that adolescent females have higher academic self‐efficacy in high school (Caprara et al., ) and report greater peer academic support (Im et al, ; Wang & Eccles, ). The MEA was equally predictive of high school graduation versus dropout status for males and females.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, when youth affiliate with peers who have low educational aspirations, their chances of graduating are lessened, regardless of their level of general motivation for educational attainment. The unique contribution of peer aspirations is consistent with extensive research demonstrating the role of peers’ school engagement and achievement on adolescents’ academic effort and achievement (Altermatt & Pomerantz, ; Im, Hughes, & West, ; Wang & Eccles, ). No evidence was found that the specific factors of valuing of education or teacher educational expectations contributed to the prediction of the high school completion outcomes above the general factor.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This support, in turn, accounts for increases in the youth’s academic competency beliefs, sense of school belonging, course grades, and classroom behavioral engagement. Middle school is typically a time of decreased academic support from peers, especially among ethnic minority and low income youth (Im, Hughes, & West, 2016), which characterizes the current sample. Findings suggest that participation in sports may stem the normative decline in perceived support from friends for prosocial norms, thereby improving youth’s engagement in school and, ultimately, educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Tanto em crianças como em adolescentes, MP tem sido relacionado a indicadores de desempenho acadêmico (Wang & Sheikh-Khalil, 2014), competência social (Marturano, Elias, & Campos, 2004;Taylor, Conger, Robins, & Widaman, 2015), resiliência (García et al, 2016) e ajustamento pessoal e social Marturano et al, 2004). Pode constituir mecanismos de proteção contra problemas de comportamento para indivíduos em risco (Véronneau & Dishion, 2010) ou expostos aos efeitos adversos da amizade com colegas academicamente desengajados (Im, Hughes, & West, 2016). O efeito protetor para comportamentos de risco está particularmente associado à percepção do adolescente sobre a supervisão dos pais (Clark, Donnellan, Robins, & Conger, 2015;Del Priore, Schlomer, & Ellis, 2017;Low & Espelage, 2014), um dado que reforça a importância da perspectiva dos filhos, assinalada recentemente em estudo sobre envolvimento parental e comportamento oposicional desafiante em crianças mais jovens, de seis a 11 anos (Li, Clark, Klump, & Burt, 2017).…”
unclassified